2000
DOI: 10.1177/0734242x0001800505
|View full text |Cite
|
Sign up to set email alerts
|

The role of aerobic activity on refuse temperature rise, I. Landfill experimental study

Abstract: The temperature field in a landfill situated in the south of France has been characterized and analysed. Sixty-four probes, measuring temperature and gas composition, were placed directly in municipal solid waste during the filling of a 200 000-m 3 cell and the spatial and temporal temperature variations recorded. The average temperature increase was about 20°C. It occurred within the first 20 days. The thermal properties of the waste (conductivity and diffusivity) were measured with a thermal shock probe.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 14 publications
(14 reference statements)
3
38
1
Order By: Relevance
“…11. The reported trend of early temperature peaks in aerobic phase followed by decreases and resulting low temperatures during anaerobic phase �Farquhar and Rovers 1973; Zanetti et al 1997;Lefebvre et al 2000� was not observed in this study. Seasonal variations may have affected the analysis of data at shallow depths in the studies reported in litera ture.…”
Section: Waste Decomposition and Thermal Conditionscontrasting
confidence: 51%
“…11. The reported trend of early temperature peaks in aerobic phase followed by decreases and resulting low temperatures during anaerobic phase �Farquhar and Rovers 1973; Zanetti et al 1997;Lefebvre et al 2000� was not observed in this study. Seasonal variations may have affected the analysis of data at shallow depths in the studies reported in litera ture.…”
Section: Waste Decomposition and Thermal Conditionscontrasting
confidence: 51%
“…It has been also found that existence of abundant quantity of organic waste labile for great metabolic activity, result generating of much heat and this rate is directly proportional to the moisture loss. As the degradation rate of waste increases, then its availability decrease, resulting heat generation rate gradually decrease [22,23,24]. In our experiment, ample vapour loss was seen in initial phase of composting process but at the end of composting phase, moisture loss decreased due to low heat generation because of consumption of almost organic matters.…”
Section: Study Of Changes In Physical Parameters Of Compost and Vermimentioning
confidence: 60%
“…It was also explore that there were 14-18°C difference between initial and final temperature of vermicompost and compost leaf litter waste while in case of control it was about 16°C ± 1°C .It has been found that initial temperature raised as a result of biochemical processes and decomposition of organic components of waste. As soon as organic waste depleted the temperature also turn down and set at lower constant value [23].…”
Section: Study Of Changes In Physical Parameters Of Compost and Vermimentioning
confidence: 99%
“…The consumption rates of O 2 and production rates of CH 4 were then used to determine the heat of biological decay of waste (Yoshida et al 1996). Lefebvre et al (2000) developed a heat generation model based on microbial aerobic decomposition. Heat generation was calculated as the temperature difference at a given time at a depth of 0.5 m and initial temperature at a depth of 0.5 m (Lefebvre et al 2000).…”
Section: Elmentioning
confidence: 99%
“…Lefebvre et al (2000) developed a heat generation model based on microbial aerobic decomposition. Heat generation was calculated as the temperature difference at a given time at a depth of 0.5 m and initial temperature at a depth of 0.5 m (Lefebvre et al 2000). Tchobanoglous et al (1993) 2 calculated assuming Ideal Gas Law applies, ρ waste = 1,000 kg/m 3 , gas production = 200 m 3 (gas)/m 3 (waste), gas composition = 60% CH4 3 calculated assuming a waste porosity = 0.4, oxygen fraction of gas in waste in as-placed condition = 21% NA = direct conversion not applied as sufficient details related to waste composition and/or timing of processes were not provided in the original reference Liu (2007) developed a method for determining heat generation based on an empirical equation dependent on time and temperature.…”
Section: Elmentioning
confidence: 99%